The scarlet and the black [videorecording (DVD)] - Peck, Gregory, 1916-2003; Plummer, Christopher; Gielgud, John, 1904-2000
Father Hugh O'Flaherty is a Vatican official who has been hiding downed Allied pilots and other enemies of the Nazi party. However, because of his high status, the Nazis cannot arrest him.